2022
DOI: 10.1590/1806-9282.20220283
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between contrast-induced nephropathy and long-term mortality after percutaneous coronary intervention in patients with chronic coronary total occlusion

Abstract: OBJECTIVE: Intervention in chronic total occlusion lesions involves long procedure time, a serious contrast load, and complex procedures. In this study, we aimed to investigate mortality rate of patients who had procedural coronary angiography done for chronic total occlusion lesions in coronary angiography series and who developed contrast-induced nephropathy. METHODS: A total of 218 patients with chronic total occlusion lesion in at least one coronary artery, from three different medical centers, who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…On average, this population is 65 years old with a body mass index of 25.6+4.0 kg/m2 and a creatinine clearance of 60.6+27.4 ml/min. V/CrCl was 3.7+2.9 in those with CIN and 2.2+1.7 in those without (p = 0.041) [17][18][19][20].…”
Section: Resultsmentioning
confidence: 93%
“…On average, this population is 65 years old with a body mass index of 25.6+4.0 kg/m2 and a creatinine clearance of 60.6+27.4 ml/min. V/CrCl was 3.7+2.9 in those with CIN and 2.2+1.7 in those without (p = 0.041) [17][18][19][20].…”
Section: Resultsmentioning
confidence: 93%
“…Studies have showed that elevated fibrinogen levels were associated with adverse clinical events in patients with CAD and diabetes. Besides, Güzel et al's study 41 found that diabetes was associated with mortality in patients with chronic total occlusion in the univariate cox analysis. What's more, diabetes may affect coronary collateral development.…”
Section: Discussionmentioning
confidence: 97%
“…All the analyzed studies had short observation periods. While various factors, including adherence issues, may affect longer-term outcomes, it is important to consider the evidence from longer-term trials [ 39 ]. Furthermore, the small sample size in each study may significantly limit the detection of secondary outcome indicators [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%